Defining the spawning season of fish in the Gulf of Tokin, Vietnam - Quoc Huy, Pham (VNU Journal of Science: Natural Sciences and Technology, 2017)
The highly pressure of fishing in spawning season and the decrease of living marine resources in the Gulf of Tonkin, require an imperative task of protection in a substainable way is to define the spawning season of the fish. The research has been conducted based on the biological datas collected from 08 fish species, primarily gathered at main fishing port in Hai Phong city and Thanh Hoa province, from May 2014 to June 2015 and the data of fish eggs and larvae in the Gulf of Tonkin between 2003 and 2016. The results has identified the spawning season of the fish in the Gulf of Tonkin has two peaks period from April to May and from July to August. In associate with the informations of sex ratios and the Gonado Somatic Index (GSI) of fish which was represented for pelagic, reefs and demersal fish, it is recommended that the fishing restriction should be apply from April to July in order to protect the fish egg and larvae in the Gulf of Tokin.